Socio-ideological fantasy and the Northern Ireland conflict : the other side - Millar, Adrian (New approaches to conflict analysis., 2006)
Analysing the conflict in Northern Ireland, this title provides an alternative psychoanalytic view as to why this conflict has defied resolution in spite of a partial cessation of violence.